Alcaloids as Part of Russian Festive Culture - Georgieva, Irina (Sledva : NBU Journal of Humanities and Arts, 2020)
The text analyses extensively the role of alcohol in Russian culture in terms of anthropology and literary history – from the traditional folklore, through 17th century texts, diary entries by Nicholas II of Russia about having champagne with the cavalry, drinking in the times of Stalin, Khrushchev, Gorbachov, in the youth subculture circles and the alcohol in some key literary texts of those periods.